Health profile of adolescents of Bhavnagar district, Gujarat, India: a cross sectional study - Bhambhani, G. D.; Bhambhani, Rutu G.; Thakor, Nilesh Chandradityasinh (International Journal of Research in Medical Sciences, 2017)
Background: Adolescence and young adulthood are periods of critical development and transition. Adolescent constitutes over 23% of the population in India. Nutrition and health needs of the adolescent are more because of more requirements for growth spurt and increase in physical activity. Objective: To study health profile of adolescents of Bhavnagar district. Methods: The study was carried by Medicine Department, K.J. Mehta Hospital, Amargadh, Bhavnagar during period from September 2014 to August 2015. After taking the permission of principals of 10 schools and consent of the parents of adolescents, 842 adolescents from 10 schools of Bhavnagar district were examined for nutritional deficiencies. The data was collected by predesign, pretested proforma and analyzed using SPSS 17.0 (Trial version). Results: Mean age was 15.8 ± 1.96 years. Out of 867, 433 (51.4%) were boys and 409 (48.6%) were girls. Vitamin A deficiency was present in 53 (6.3%) adolescents. Vitamin B complex deficiency signs were seen in 139 (16.5%) adolescents. Vitamin C deficiency signs were seen in 84 (10.0%) adolescents. PEM was observed in 90 (10.7%) adolescents. The study revealed that 67.0% girls were suffering from anaemia compare to 58.7% of boys. 117 (13.9%) adolescents had visual impairment. Conclusions: Poor personal hygiene and nutritional deficiency among these adolescents needs great attention and health education.